Pelaksanaan Pengelolaan Administrasi Guru Dalam Meningkatan Mutu Pendidikan - Wahyu Setyo Nugroho (Universitas Sains dan Teknologi Komputer, 2024)
Teacher administration is an important aspect in the implementation of education, because teacher management is a strategic factor that has a big influence on improving the quality of education. The main problem in this research is